Pengaruh Tingkat Pendidikan, Pengalaman, dan Pemanfaatan Teknologi Informasi Akuntansi Pada Penerapan Sak Etap - Puspa Widiani, Ni Wayan Zenny; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2017)
This study aims to determine the effect of education level, manager experience, and utilization of accounting information technology on the application of SAK ETAP on the cooperative savings and loan the City of Denpasar. This research was conducted in Denpasar City with the object of research is education level, manager experience, utilization of accounting information technology and application of SAK ETAP. The number of samples used is 46 managers. Data were collected by distributing questionnaires analyzed by using multiple linear regression analysis. Data were collected by distributing questionnaires analyzed by using multiple linear regression analysis. The level of manager's education, managerial experience and utilization of accounting information technology have a positive influence on the application of SAK ETAP in the Denpasar saving and loan cooperative.  Keywords:  evel of education, experience, utilization of information technology, application of SAK ETAP